One-Input Three-Output Current-Mode Universal Filter Using Translinear Current Conveyors - Montree Kumngern (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2019)
This paper presents a new current-mode universal filter with one-input three-output employing three translinear current conveyors and two grounded capacitors. The proposed filter provides low-pass, band-pass, high-pass current response with high output impedance output which can be directly connected for current-mode circuit. The band-pass and all-pass filters can also be obtained. The parameters wo and Q can be controlled separately and electronically by the bias currents of current conveyors. For realizing all filtering functions, no passive and active matching conditions are required. The active and passive sensitivities are low. The characteristic of the proposed circuit can be confirmed by SPICE simulations.